Analysis of Morphological Acquisition in Second-Grade Elementary School Students: A Psycholinguistic Study in Language Learning - Indah Afrianti; Rusdin; Ika Amelia (JURNAL PENDIDIKAN & PENGAJARAN (JUPE2), 2026)
Language acquisition is a natural process experienced by children in developing their linguistic abilities, including morphological acquisition. However, elementary school students still frequently encounter difficulties in using standard Indonesian morphological forms in daily communication and classroom learning activities. This study aims to analyze the morphological acquisition of second-grade elementary school students from a psycholinguistic perspective, focusing on the use of affixation, reduplication, word simplification, and regional language interference in language learning. This study employed a qualitative descriptive approach conducted at SDN 11 Dompu. The participants consisted of five second-grade students selected through purposive sampling. Data were collected through classroom observations, interviews, recordings of students’ conversations, and documentation during learning activities and daily interactions at school. The data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that students were able to use various morphological forms such as root words, affixed words, and reduplication, although several morphological and phonological deviations were still found, including affix omission, verb simplification, phoneme deletion, and regional language interference. Environmental exposure, peer interaction, and the use of informal language strongly influenced students’ language production. From a psycholinguistic perspective, students’ language acquisition reflects the interaction between cognitive development, linguistic competence, and social environment. This study contributes to psycholinguistic research and provides practical implications for improving Indonesian language learning strategies in elementary schools, particularly in strengthening students’ mastery of standard morphology in spoken and written communication.